Bound for the algebraic connectivity of Nordhaus-Gaddum type for unicyclic graphs(单圈图的N-G型的代数连通度的界) - LüDa-mei(吕大梅); LüJia-jun(吕嘉钧) (Zhejiang Daxue xuebao. Lixue ban, 2006)
对任一个n阶单图G，用a(G)表示G的代数连通度，证明了对任一n阶单圈图G，有1 ≤ a(G)+a(Gc).